Effect of total mixed ration (TM R) briquettes on milk yield, composition and sensory properties of cow milk - KARUNANAYAKA, R H W M; NAYANANJALIE, W A D; WEERASINGHA, W V V R; SOMASIRI, S C; KUMARI, M A A P; ADIKARI, A M J B; MANGALIKA, U L P; SUNDARABARATHY, T V (The Indian Journal of Animal Sciences, 2022)
The current study aimed to assess the effect of feeding total mix ration (TMR) briquettes on milk composition, yield and sensory attributes. Jersey × Sahiwal crossbred cows (Nine) were randomly assigned to three treatments (CTL: guinea grass with commercial feed, TMR1 and TMR2: TMR briquettes) in a 3 × 3 replicated Latin square design. Daily milk yield was recorded and milk composition was measured at three days intervals. At the end of each period, fatty acid composition, calcium, phosphorus and sensory properties of milk were analysed. Milk yield trended to be higher in cows fed with TMR briquettes and milk fat content was similar among the treatments. There was no significant difference in milk fatty acid profile among the treatments; however, lauric acid (C12:0) concentration was significantly higher in milk obtained from the cows fed with TMR1 briquettes. Milk calcium and phosphorus contents did not show any significant difference. All the sensory attributes were significantly higher in milk tested from cows fed with TMR1. The present study revealed that feeding TMR1 briquette could be one of the strategies to overcome the inconsistent milk yield reported during the forage scare periods without affecting the milk composition, and fatty acid composition with better sensory attributes.